Installations Using Resonant Pulse Compression for Generating Ultra-Short High Power Pulses in X-, K- and Q-band - Chumerin P. Yu.; Man’ko A. N.; Slinko V. N.; Yushkov Y. G. Yuri Georgievich (High power microwaves, 2004)
Title from the title-page.